Advanced life support (ALS) instructors experience of ALS education in Western Australia: A qualitative exploratory research study - Taplin, John; McConigley, Ruth (Churchill Livingstone, 2015)
Background: When cardiac arrest occurs, timely competent advanced life support (ALS) interventions by nursing staff can influence patient outcomes. Ongoing ALS education influences maintenance of competency and avoids skill decay. Objectives: To explore the methods of ALS education delivery for nurses in the workplace; describe the issues relating to maintaining ALS competency; explore ALS competency decay for nurses and develop recommendations for the provision of continuing ALS education. Design: A qualitative exploratory design was used to study ALS education provision in the workplace. Participants: Data were collected from ALS nurse experts in Western Australia by face-to-face and phone interviews. Methods: Semi-structured interviews were conducted and organised around a set of predetermined questions. Results: Two major themes were identified; the first theme Demand and Supply describes the increasing demand for ALS education for nurses and the challenges with providing timely cost effective traditional face-to-face ALS education. The second theme, Choosing The Best Education Options describes new ways to provide ALS education using emerging technologies. Conclusions: The study suggested that using e-learning methods would assist with educating the maximum amount of nurses in a timely manner and e-learning and teleconferencing offer opportunities to reach nurses in distant locations. Delivering ALS education more frequently than annually would increase skills maintenance and lessen skill decay. Further research is required to explore which blended e-learning model is best suited to ALS education.